GENERAL ELEMENTS OF RISK MANAGEMENT - Kubanova, Jaroslava (Doprava a spoje, 2011)
With the gradual evolution of human society increases the importance and status of traffic. However, with increasing intensity and volume of road transport tends to be constant and its accompanying negative signs have been associated with establishment and operation of an efficient transport system. The article points to the general elements of risk management, which affect the operation of the transport company.